ANALISIS UNSUR INTRINSIK DAN NILAI MORAL DALAM NASKAH KETOPRAK SEMBOJA KAPUGERAN KARYA BONDAN NUSANTARA - Alifah Ronna Anggraeni; Raheni Suhita; Favorita Kurwidaria (Sabdasastra : Jurnal Pendidikan Bahasa Jawa, 2020)
This research aims to analyze structural and moral value in the manuscript of The Semboja Kapugeran ketoprak by Bondan Nusantara. Using qualitative, this research uses descriptive methods of analysis in order to obtain the results of the analysis as expected. The elements analyzed in this study are plot, characterization, settings, theme and message. The results showed there were eleven symbolic figures and their respective characters, the script has an advanced plot consisting of exposition, complications, climax and falling action. It's about a romance that's motivated by a family grudge. The message that can be taken is that revenge will only bring havoc in life.